The Life-cycle Impact of Alternative Higher Education Finance Systems in Ireland - Flannery, Darren; O'Donoghue, Cathal (Economic & Social Studies, 2011)
With increasing numbers of young people participating in higher education in Ireland and a heavy reliance of higher education institutions on State funding, the introduction of an alternative finance system for Ireland has been muted over the past number of years. However, no study has been conducted to gauge the potential impact of such measures. In this paper we utilise a dynamic microsimulation model developed for Ireland to simulate the impact of both an income contingent loan system (ICL) and a graduate tax system from a fiscal and redistributional viewpoint and to analyse the repayment length under the former system. Our results suggest that an ICL system could be more equitable, while the graduate tax system could be a better alternative from a fiscal viewpoint. The results also illustrate the importance of the interest rate attached to any future student loan system within Ireland from a fiscal viewpoint.
Keywords: Higher education; finance; Ireland